2022
DOI: 10.1088/1361-6463/ac79de
|View full text |Cite
|
Sign up to set email alerts
|

Inverted spike-rate-dependent plasticity due to charge traps in a metal-oxide memristive device

Abstract: We develop a model of Au/Ta/ZrO2(Y)/Ta2O5/TiN/Ti memristive devices, and demonstrate, both experimentally and numerically, an inverted spike-rate-dependent plasticity effect. The effect consists in the reduction of the learning rate with the increase in frequency of spikes generated by the phase-locked loop neuron. The memristor model uses two internal state variables representing the number of complete filaments and concentration of charged traps. While the former state variable defines the device resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 38 publications
0
2
0
1
Order By: Relevance
“…Memristive nanodevices, such as resistive RAMs, memristors [20], or adaptive transistors [21], can provide the compact synapses required for more advanced neuromorphic circuits. Recent studies have demonstrated that these devices can replicate biological synapses' learning rules, such as spike timing-dependent plasticity (STDP), and even more complex plasticity rules crucial for brain-inspired learning [26][27][28][29][30]. By combining memristive synapses with CMOS neurons (or potentially memristor-based neurons in the future [31]), significant advancements in computing and highly efficient cognitive tasks could be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Memristive nanodevices, such as resistive RAMs, memristors [20], or adaptive transistors [21], can provide the compact synapses required for more advanced neuromorphic circuits. Recent studies have demonstrated that these devices can replicate biological synapses' learning rules, such as spike timing-dependent plasticity (STDP), and even more complex plasticity rules crucial for brain-inspired learning [26][27][28][29][30]. By combining memristive synapses with CMOS neurons (or potentially memristor-based neurons in the future [31]), significant advancements in computing and highly efficient cognitive tasks could be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Such architectures can rely on the rich dynamics of memristive devices and the self-organization of plastic memristive connections. [9] Their similarity to the living brain architectures will make it possible to take the next step towards the hybrid intelligence based on the symbiosis of electronic and biological subsystems. [10,11] In addition, there are many other applications, including stochastic computing and probabilistic networks, as well as hardware information security primitives, [12][13][14] in which memristive devices act as the sources of randomness and entropy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, two neuron-type generators connected by a memristive element were shown to be capable of synchronization. This synchronization between two coupled neuron-like generators is transient and highly reliant on the present condition of the memristive element [5].…”
mentioning
confidence: 99%
“…Кроме того, продемонстрирована синхронизация двух нейроноподобных генераторов, связанных через мемристический элемент. Эта синхронизация носит временный характер и сильно зависит от текущего состояния мемристивного элемента [5].…”
unclassified